The Nurse as Bricoleur in Falls Prevention: Learning from a Case Study of the Implementation of Fall Prevention Best Practices. (10th March 2014) - Kirkpatrick, Helen; Boblin, Sheryl; Ireland, Sandra; Robertson, Kim
ABSTRACT Background Falls prevention in "real‐life" clinical practice is a complex undertaking. Nurses play an active and essential role in falls prevention. Aim This discussion paper presents a picture of the nurse as a bricoleur in falls prevention, requiring knowledge in many areas and the ability to perform multiple diverse tasks. Methods Building on a qualitative case study with nurses at various levels in three acute care facilities, this paper posits that the concept of nurse as bricoleur has the potential to broaden our understanding of the complexity of falls prevention. Findings The nurse as bricoleur within the Promoting Action Research in Health Services framework as the provider of person‐ or patient‐centered evidence‐based care is conceptualized. Within this framework, the nurse uses his or her professional knowledge or clinical experience while considering research, local data, and information, and the patient's experience and preferences to provide this care, the bricolage. Each of these areas is discussed as well as the impact on the nurse when a fall does occur. Linking Evidence to Action Recognizing this complexity of the nurses' world has important implications for both service delivery and education, including preparation of students, and the implementation of new organizational initiatives and supports for nurses when falls do occur despite the best efforts of all involved.